Financial Performance Analysis Using Economic Value Added and Market Value Added Methods - Ariefah SUNDARI; Ahmad Fathur ROZI; Ana Fitriyatul BILGIES; Ali MUHAJIR (Journal of Tourism Economics and Policy, 2023)
This study aims to determine and analyze financial performance with the Economic Value Added and Market Value Added methods in the Cement Sub-sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The research method used is a quantitative method with a descriptive approach and the sampling technique in this study is a purposive sampling technique. The data collection techniques used used secondary data through library studies and documentation studies obtained through the website https://www.idx.co.id in the form of a Balance Sheet and Profit and Loss Report for the Year 2017-2021. The results of this study are that the three cement companies have a positive EVA value which means they have succeeded in creating economic value, and one company has a negative EVA value at PT Semen Baturaja Tbk which means the company is not able to provide added value in 2021. means providing added value through market capitalization value.